EVALUASI EFEKTIVITAS PROGRAM PELATIHAN GURU DI GUGUS 06 KECAMATAN SERPONG KOTA TANGERANG SELATAN - Asih, Dini Aini Dewi; Mardisentosa, Bambang; Hardian, Dafyar Eliadi (Perspektif : Jurnal Ilmu Administrasi, 2025)
This study evaluates the effectiveness of the KOSP Workshop teacher training programme and the implementation of P5 in Cluster 06, Serpong District, South Tangerang City, with a case study at SDN Cilenggang 04. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model from Stufflebeam (2003) and effectiveness indicators according to Sutrisno (2010), including programme understanding, on-target, on-time, goal achievement, and tangible change. Data were collected through interviews with key informants, including school supervisors, teachers, parents, and students, then analysed qualitatively. The results showed that the training programme was effective in improving teachers' conceptual understanding of KOSP and P5, in line with the needs of the Independent Curriculum and the Pancasila Student Profile. Teachers were actively involved in discussions, simulations, and presentations, although technical implementation in the classroom still requires ongoing guidance. The programme was relevant, implemented on time, and achieved its short-term objectives, with increased teacher competence, creativity, and proactive attitudes in developing learning. However, several aspects need to be strengthened, including continued mentoring, expanding the training duration, updating modules based on local wisdom projects, strengthening teacher collaboration, and increasing parent and community involvement. Integrating these recommendations is expected to optimise the programme's long-term impact, improve teacher capacity, and encourage creativity and student learning outcomes. Keywords: teacher training, programme evaluation, CIPP, effectiveness, Stufflebeam.